Materials Chemistry - Fahlman, Bradley D.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2018)
The 3rd edition continues to build on the strengths that were recognized by a 2008 Textbook Excellence Award from the Text and Academic Authors Association (TAA). Materials Chemistry addresses inorganic-, organic-, and nano-based materials from a structure vs. property treatment, providing a suitable breadth and depth coverage of the rapidly evolving materials field - in a concise format. The 3rd edition offers significant updates throughout, with expanded sections on sustainability, energy storage, metal-organic frameworks, solid electrolytes, solvothermal/microwave syntheses, integrated circuits, and nanotoxicity. Most appropriate for Junior/Senior undergraduate students, as well as first-year graduate students in chemistry, physics, or engineering fields, Materials Chemistry may also serve as a valuable reference to industrial researchers. Each chapter concludes with a section that describes important materials applications, and an updated list of thought-provoking questions.
1. What is Materials Chemistry?. - 2. Solid-State Chemistry -- 3. Metals -- 4. Semiconductors -- 5. Polymeric Materials -- 6. Nanomaterials -- 7. Materials Characterization -- Appendices I, II, III.
Keywords: Materials -- Analysis; Polymers; Condensed matter; Materials; Nanotechnology; Spectrum analysis; Characterization and Analytical Technique; Polymers; Condensed Matter Physics; Materials Engineering; Nanotechnology; Spectroscopy